2021
DOI: 10.3390/jcm10214988
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Growth Hormone Deficiency and Idiopathic Short Stature: Comparative Efficiency after Growth Hormone Treatment up to Adult Height

Abstract: Introduction: Treatment with growth hormone (GH) is not approved for idiopathic short stature (ISS) in Europe. Objectives: To compare the growth of children treated with isolated GH deficiency (IGHD) vs. ISS-treated and untreated children. Methods: A retrospective descriptive study of patients treated in the last 14 years for IGHD (Group A), in comparison with ISS-treated (Group B) and untreated (Group C) subjects. Results: Group A had 67 males, who showed a height gain of 1.24 SD. Group B had 30 boys, who sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Currently, there is much debate about the treatment of ISS with recombinant human GH (rhGH). Although it brings the expected benefits in terms of improving final height, it seems that the search for the causes of ISS and their subsequent elimination may reduce the costs and psychological burden of such treatment [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is much debate about the treatment of ISS with recombinant human GH (rhGH). Although it brings the expected benefits in terms of improving final height, it seems that the search for the causes of ISS and their subsequent elimination may reduce the costs and psychological burden of such treatment [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 However, the European Agency for the Evaluation of Medicinal Products Europe is yet to approve using GH for ISS because available data is affected by several biases, including using a wide variety of doses and relatively small study cohorts. 14 GH is an expansive biotechnology originally designed for treating GH deficiency, 13 and increasing growth to achieve an adult height within the target height range for the individual is the primary treatment goal. 15,16 The expansion of GH therapy to include ISS is facilitated by pediatric endocrinologists and supported by the producing companies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the European Agency for the Evaluation of Medicinal Products Europe is yet to approve using GH for ISS because available data is affected by several biases, including using a wide variety of doses and relatively small study cohorts. 14…”
Section: Introductionmentioning
confidence: 99%
“…We believe that a potential future study suggested by Bright et al [2], i.e., to identify “predictive enrichment markers” to increase the number of true-positive and true-negative diagnoses of GHD by analysing the response to rhGH treatment in a physiological dosage in children with various percentiles of growth response, is challenging. It is not only difficult to assess what constitutes “physiologic replacement,” and what constitutes “amelioration of clinical sequelae”, but one should also realize that the growth response to rhGH of children with partial GHD is similar to that of children with ISS [22]. In Europe, ISS is not an approved indication for rhGH treatment.…”
mentioning
confidence: 99%